Faktor-Faktor Yang Mempengaruhi Efektivitas Kelembagaan Petani (Kasus di Provinsi Jawa Tengah) - Sapja Anantanyu; Sumardjo Sumardjo; Margono Slamet; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2009)
The effectiveness farmer’s institutions were needed for the agricultural development in globalization economic era. Economic indicators, agricultural infrastructures, and government policy often cause small farmer to economical and social marginalized. On the other side, farmer’s institutions which are expected be able to strengthen the farmer position to face the existing problems not effectively yet. The purpose of this research are to: (1) Identify and explain various factors have affected on the effectiveness of farmer’s institution, and (2) Formulate an appropriate strategy in capacity building of farmer’s institution. This Research was conducted at three district of Center Java Province, there are: Klaten, Grobogan, and Karanganyar. The result shows that effectiveness of farmer’s institution is still at medium category. Effectiveness of farmer’s institution was directly influenced by level of member’s participation in farmer’s institution, outsider role, formal education, and local leadership. Famer’s income, the quality of extension, social participation, needs, and capacities level of farmer were indirectly influenced to the effectiveness of farmer’s institution by participation in farmer’s institution. Learning experience of famer indirectly influences to the effectiveness of farmer’s institution by capacities level of farmer. The quality of agricultural extension, directly and indirectly, influences to the farmer’s capacities. It increases their participation in farmer’s institution and push their institution effectiveness.